Tecknade serier som feministisk aktivism: Kvinnor ritar bara serier om mens och Draw the Line - Nordenstam, Anna; Wallin Wictorin, Margareta (Tidskrift för litteraturvetenskap, 2020)
Comics as Feminist Activism: Kvinnor ritar bara serier om mens and Draw the Line The aim of the article is to discuss the two Swedish comics anthologies Kvinnor ritar bara serier om mens [Women only draw comics on menstruation] (2014) and Draw the Line (2018) as feminist activism (Felshin 1995; Liinason and Cuesta 2016. The editors were inspired by two important events, a radio program by the Swedish comics artist Liv Strömquist in 2013, and the #metoo movement that started in 2017. By analysing some strategic samples, the article examines why and how the comics anthologies were produced, and how they have been used. The analysis of the comics, and especially the close readings of Biller’s and Lucassi’s comics, show how the artists used a combination of verbal text and narrative drawing (Groensteen 2008; Baetens 2011) to visualize emotions and crucial problems, give them public attention, talk back, and contribute to change. The anthologies were produced in collaborative processes, got transferred into other cultural media and have been used for empowering and educational purposes. Keywords: , , ,, ,